2013
DOI: 10.17221/56/2011-pps
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of selected plant powders against Prostephanus truncatus (Coleoptera: Bostrichidae) in stored maize grains

Abstract: Chebet F., Deng A.L., Ogendo J.O, Kamau A.W., Bett P.K. (2013)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
4
29
0
Order By: Relevance
“…Each plant powder was evaluated at four rates (2,5,7, and 10% w/w) and commercial synthetic insecticide Antouka (Permethrin 3 g/kg + pirimiphos 16 g/kg; DP) included as a positive control. Treated and untreated yam chips (10 g) were alternately placed equidistantly from the center of the circular base [20]. The treatments were arranged in a completely randomized block design with four replicates per concentration.…”
Section: Repellent Activity Of Leaf Powdermentioning
confidence: 99%
See 1 more Smart Citation
“…Each plant powder was evaluated at four rates (2,5,7, and 10% w/w) and commercial synthetic insecticide Antouka (Permethrin 3 g/kg + pirimiphos 16 g/kg; DP) included as a positive control. Treated and untreated yam chips (10 g) were alternately placed equidistantly from the center of the circular base [20]. The treatments were arranged in a completely randomized block design with four replicates per concentration.…”
Section: Repellent Activity Of Leaf Powdermentioning
confidence: 99%
“…The experiment was carried out following the methodology used by Chebet et al [20]. Leaf powders of the different plants were admixed with 100 g of disinfected yam chips in plastic jars (13 cm in diameter by 10 cm in height) at, respectively, rates (% w/w) of 0, 2, 4, 6, 8, and 10.…”
Section: Contact Toxicity Of Plant Powdersmentioning
confidence: 99%
“…In addition, active phytochemicals such as alkaloids have been found to disrupt growth and reduce larval survival by hindering loss of exoskeleton during larval development [47]. Other active principles such as isoflavonoids, flavonoids and terpenoids have also been reported to inhibit reproduction and fertility among coleopterons [29,48].…”
Section: Concentration (%Extract) Pr (Mean% ± Se)mentioning
confidence: 99%
“…Bioactivity of plant extracts on adults Sharma (1999) reported that neem seed, neem kernel powder at 4 % and neem leaf powder at 5 % concentration protected maize for 5 months against S. oryzae, S. cerealella, R. dominica and T. castaneum. Also many studies have shown the effectiveness of neem against storage insects of maize (Huang and Ho 1998;Mulungu et al 2007;Sule et al 2012;Chebet et al 2013). Li et al (2000) reported that isolated fraction from leaf of Eupatorium adenophorum Spreng.…”
Section: Introductionmentioning
confidence: 99%